Development Strategy of PPM al-Kautsar Micro Waqf Bank in Lima Puluh Kota Regency - Nurhafiani Nurhafiani; Azhari Akmal Tarigan; Muhammad Yafiz (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2022)
This research aims to find out and analyze the development strategy of the PPM Al-Kautsar Micro Waqf Bank in the Lima Puluh Kota Regency. The data analysis technique used is the SWOT analysis method (Strenght, Weakness, Opportunity, Threats). Based on the results of the SWOT matrix analysis, it is known that the strategy that can be carried out in developing a Micro Waqf Bank is stratetgi SO by using all strengths to take advantage of existing opportunities. The strategy is consistency of low mentoring services (ju'alah, without collateral and interest by utilizing government restructuring programs, utilizing the role of kyai in establishing good cooperation and building trust with institutions, local governments, the community socializing the existence of Micro Waqf Bank, carrying out Halmi routines during a pandemic virtually and directly by complying with health protocols in providing education, direction, education to customers, improving the quality of services and products even though it already exists with a ball pick-up system, optimizing the empowerment of mentoring through digital so that customers can survive during the pandemic despite social restrictions but empowerment continues to run. The strategy of developing Micro Waqf Bank is to use Micro Waqf Bank digitalization in providing virtual education, promoting customer products through e-commerce and social media, utilizing the role of kiyai in socializing BWM programs to the community